Safety Assessment of Electromagnetic Exposure for 24 GHz Anticollision Antenna Mounted on the Side of Electric Vehicle - Guiyu Xie; Mai Lu (International Journal of Antennas and Propagation)
This study aims to investigate the effects of radio frequency electromagnetic field (RF-EMF) generated by 24 GHz anticollision antennas on passengers and pedestrians under exposure from different numbers of the antenna, each fed with 0.1 W. The proposed array antenna operates from 23.75 to 24.15 GHz with high gain for 21.7 dBi and low sidelobe level for −20 dB at 24 GHz, which can meet the design requirements of automotive anticollision radar antenna. By means of computational dosimetry, the specific absorption rate (SAR) distribution, the whole-body average SAR (SARwb), the absorbed power density (Sab), the temperature rises on surface and cross-section of human head are calculated for measuring RF-EMF doses of passengers and pedestrians. In all exposure scenarios where the passengers are exposed to the antenna radiation, the SARwb value and the Sab value of the driver are the largest. In the single-antenna exposure scenario, the SARwb value is 1.67 × 10−6 W/kg and the Sab value is 0.97 W/m2. In the two-antenna exposure scenario, the SARwb value is 1.56 × 10−5 W/kg and the Sab value is 1.8356 W/m2. In the four-antenna exposure scenario, the SARwb value is 1.50 × 10−5 W/kg and the Sab value is 2.7301 W/m2. In all exposure scenarios where the pedestrians are exposed to the antenna radiation, the SARwb value of the rear pedestrian frontal to the antenna is the largest with 2.68 × 10−8 W/kg. Moreover, the Sab value of the front pedestrian frontal to the antenna is the largest with 0.00289 W/m2. And the maximum local temperature rises on human heads of passengers and pedestrians are all 0.220°C. In a word, all calculated values are well below the International Commission on Nonionizing Radiation Protection (ICNIRP) basic restrictions and reference levels.